ANALISIS PENGARUH KUALITAS PELAYANAN DAN CITRA INSTITUSI TERHADAP KEPUASAN MAHASISWA UNIVERSITAS MUARO BUNGO, JAMBI - Effendi, Nur Ika (Universitas Putra Indonesia YPTK Padang, 2015)
AbstractThe aim of this research is to analyze the impact variables of ervice quality andinstitution image on satisfaction and loyalty of the student of Universitas Muara Bungoin Jambi. this research use a survey method, the data is collected by havingquestionnaires of 200 respondents. The population of this research is 1591 students ofumb that were odd semester, academic year 2013/2014. The sampling method of thisresearch is proportionate sampling from customers of 11 division, then, the data isanalyzed with structural equation modelling (SEM) under AMOS (Analysis of MomentServives) 18.0 computer program with maximum Likelihood estimation.From dataanalaysis obtained by result where model raised in this research acceptable. the resultshowed that the model of this research has fulfilled the goooness of fit from chi square145.154, GFI 0.95, TLI 0.905, CFI 0.929, RMSEA 0.087. Result of examinationobtained that: 1. Service quality had positive effect on institution image with cr 6.821cr > ? 0,05 t table = 1.64. Institution image had positive effect on satisfaction with cr2.924 cr > ? 0,05 t tabel = 1.64. 2. Service quality did not effect on satisfaction withCR 0.219 CR > ? 0,05 t table = 1.64. Service quality, institution image, had positiveeffect on satisfaction with cr 0,2466. 3. Service quality had positive effect onsatisfaction trough institution image 1,5039.Keyword : University of Muara Bungo, Service Quality, InstitutionImage,Satisfaction